LINGUO-CULTURAL FEATURES OF JEWELRY NAMES IN THE UZBEK, GERMAN AND RUSSIAN LANGUAGES AND THE SPECIFICITY OF THEIR TRANSLATION FROM THE UZBEK LANGUAGE - Alimov, Tohir (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article studies the features of the translation of the names of some types of jewelry and related lexemes into Uzbek, German and Russian in a comparative aspect. For the correct translation into German and Russian of jewelry and related lexical units related to Uzbek culture, it is important to have a good knowledge of the customs, images and names of household items of the Uzbek people. The names of the Uzbek national ornaments analyzed in the article have equivalents in German and Russian, and although they differ in form, they are close to each other in their semantic structure. The article notes the relevance of the correct interpretation of the object names for successful communication.
Keywords: jewelry; word; lexeme; term; translation; Uzbek; German; Russian; research